2016
DOI: 10.7567/jjap.55.07lg04
|View full text |Cite
|
Sign up to set email alerts
|

Roles of charged particles and reactive species on cell membrane permeabilization induced by atmospheric-pressure plasma irradiation

Abstract: As factors that influence cell membrane permeabilization during direct and indirect atmospheric-pressure plasma irradiation, charged particle influx, superoxide anion radicals (O2 −∙), and hydrogen peroxide (H2O2) in plasma-irradiated solution were evaluated. These are the three strong candidate factors and might multiply contribute to cell membrane permeabilization. In particular, a shorter plasma diffusion distance leads to the enhancement of the direct effects such as charged particle infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…( 36 38 ) Furthermore, the use of fluorescent dyes such as YOYO-1 and LIVE/DEAD Stain indicated that APP irradiation enhances the permeability of the cell membrane without killing the cell. ( 39 42 ) To understand the underlying mechanism of cell membrane permeabilization, we have investigated the effects of plasma-produced reactive species in the liquid phase region on cell activity. These plasma-produced reactive species reportedly play key roles in many medical applications of GLI-APPJ.…”
Section: Cell Membrane Permeabilization By Gas-liquid Interfacial Atmmentioning
confidence: 99%
See 2 more Smart Citations
“…( 36 38 ) Furthermore, the use of fluorescent dyes such as YOYO-1 and LIVE/DEAD Stain indicated that APP irradiation enhances the permeability of the cell membrane without killing the cell. ( 39 42 ) To understand the underlying mechanism of cell membrane permeabilization, we have investigated the effects of plasma-produced reactive species in the liquid phase region on cell activity. These plasma-produced reactive species reportedly play key roles in many medical applications of GLI-APPJ.…”
Section: Cell Membrane Permeabilization By Gas-liquid Interfacial Atmmentioning
confidence: 99%
“…To identify these direct and indirect irradiation effects, we detect • OH and superoxide anion radicals O 2 •− in plasma-irradiated water using ESR. ( 65 67 ) The half-life of O 2 •− is several tens of minutes in plasma-irradiated water at 4°C ( 42 ) and O 2 •− is therefore a strong candidate as the short-lived key-product. The generation of O 2 •− in water by APPJ irradiation is detected by ESR using 5-(2,2-dimethyl-1,3-propoxycyclophosphoryl)-5-methyl-1-pyrroline N -oxide) (CYPMPO) as spin-trap because the reaction rate of CYPMPO with O 2 •− is higher than that of the more commonly used 5,5-dimethyl N -oxide pyrroline (DMPO).…”
Section: Cell Membrane Permeabilization By Gas-liquid Interfacial Atmmentioning
confidence: 99%
See 1 more Smart Citation
“…Among APP medical applications, transfection technology of middle‐size (500–30 000 Da) and large‐size (30 000‐ Da) molecules has attracted attention. Some research groups have reported cell membrane permeabilization of middle‐size fluorescent dye and large‐size plasmid DNA using various types of APP . Although a few reports have suggested that the multiple effects of electric and chemical stimuli are key factors in APP‐induced membrane permeabilization, most of the underlying mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Kvam et al reported that cold plasma could damage cell membrane integrity in a time-dependent manner 64) . Of note, a current cold plasma study indicated that the synergistic actions of charged particles and chemical reactive species damaged cell membrane 65) . The SEM results in Fig.…”
Section: Discussionmentioning
confidence: 99%